Synthesis and carbonic anhydrase I, II, IX and XII inhibitory activity of sulfamates incorporating piperazinyl-ureido moieties. Issue 17 (1st September 2015) - Congiu, Cenzo; Onnis, Valentina; Deplano, Alessandro; Balboni, Gianfranco; Ceruso, Mariangela; Supuran, Claudiu T.
Graphical abstract: R = Ph, benzyl, substituted aryl; etc. K I (hCA I) = 9.4–896.8 nM; K I (hCA II) = 1.0–1427 nM; K I (hCA IX) = 0.91–120.7 nM; K I (hCA XII) = 1.0–84.5 nM. Abstract: A series of sulfamates were synthesized using as lead compound SLC-0111, a sulfonamide carbonic anhydrase (CA, EC 4.2.1.1) inhibitor in Phase I clinical trials. The new derivatives incorporated ureido moieties as spacers between the benzene sulfamate fragment which binds the zinc ion from the active site, and the tail of the inhibitor, but the urea moieties were part of a substituted piperazine ring system. The derivatives (and some of their phenol precursors) were tested for the inhibition of the cytosolic, hCA I and II (off target isoforms) and the trans-membrane, tumor-associated hCA IX and XII enzymes (anticancer drug targets). Generally hCA I was not effectively inhibited, whereas many low nanomolar inhibitors were evidenced against hCA II ( K I s in the range of 1.0–94.4 nM), IX ( K I s in the range of 0.91–36.9 nM), and XII ( K I s in the range of 1.0–84.5 nM). The best substitution fragments at the piperazine ring included the following moieties: 3-methylphenyl, 2, 3-dimethylphenyl, 4-methoxyphenyl, 6-arylpyrimidine-2-yl.